Rivaroxaban versus warfarin and dabigatran in atrial fibrillation: comparative effectiveness and safety in Danish routine care†. Issue 11 (27th May 2016) - Gorst‐Rasmussen, Anders; Lip, Gregory Y. H.; Bjerregaard Larsen, Torben
Abstract: Purpose: To evaluate effectiveness and safety of rivaroxaban versus warfarin or dabigatran etexilate in a prospective cohort of routine care non‐valvular atrial fibrillation (AF) patients during February 2012 to August 2014. Methods: We identified in nationwide health registries a cohort of AF patients who were new‐users of rivaroxaban 15 mg (R15) or 20 mg (R20); dabigatran 110 mg (D110) or 150 mg (D150); or warfarin. Propensity‐adjusted Cox regression was used to compare outcome rates in four settings: 'R15 vs. warfarin'; 'R15 vs. D110'; 'R20 vs. warfarin'; and 'R20 vs. D150'. Results: Rivaroxaban users (R15: n  = 776; R20: n  = 1629) were older and with more comorbidities than warfarin ( n  = 11 045) and dabigatran users (D110: n  = 3588; D150: n  = 5320). Rivaroxaban 15‐mg users had the overall highest crude mortality rate. After propensity adjustment, rivaroxaban had lower stroke rates vs. warfarin (R15: hazard ratio [HR] 0.46, 95% confidence interval [CI]: 0.26–0.82; R20 HR: 0.72, 95%CI: 0.51–1.01), and similar stroke rates vs. dabigatran. The bleeding rate was similar to warfarin and moderately higher vs. dabigatran (R15 vs. D110 HR: 1.28, 95%CI: 0.82–2.01; R20 vs. D150 HR: 1.81, 95%CI: 1.25–2.62). The mortality rate was higher vs. dabigatran (R15 vs. D110 HR: 1.43, 95%CI: 1.13–1.81; R20 vs. D150 HR: 1.52, 95%CI: 1.06–2.19). Conclusions: Rivaroxaban was associated with similar or lower stroke rates, but higher bleeding and mortality rates. Channeling of rivaroxaban towards elderly and less healthy patients may have generated residual confounding. In particular, our findings cannot stand alone when deciding which oral anticoagulant to prescribe. Copyright © 2016 John Wiley & Sons, Ltd.